Galectin-9 gene (LGALS9) polymorphisms are associated with rheumatoid arthritis in Brazilian patients - Vilar, Kamila de Melo (PLoS One, 2019)
INTRODUCTION: Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by synovial inflammation and hyperplasia, as well as cartilage and bone destruction. Several proteins are associated with the pathogenesis of the disease. Galectin-9 belongs to the family of lectins that are involved in various biological processes and have anti-inflammatory activity. OBJECTIVE: To investigate associations between the SNPs of the GAL-9 gene (LGALS9) and serum levels in rheumatoid arthritis patients. We extracted DNA from 356 subjects, 156 RA patients and 200 healthy controls from northeastern Brazil. Three polymorphisms (rs4795835, rs3763959, and rs4239242) in the LGALS9 gene were selected and genotyped using TaqMan SNP genotyping assay. Serum concentrations of galectin-9 were analyzed by ELISA. RESULTS: The rs4239242 TT genotype showed a positive association with RA (p = 0.0032, odds ratio = 0.28), and heterozygous TC were prevalent in the control group compared to RA patients (p = 0.0001, odds ratio = 7.99). Galectin-9 serum levels were significantly increased in RA patients compared to the control group (p<0.0001). Patients in remission had high levels of galectin compared to the moderate activity group (p<0.0001). Regarding the Clinical Disease Activity Index (CDAI), patients in remission or low activity presented high levels of galectin when compared to patients in severity (p<0.0001). Patients performing moderate activity had a significant value compared to patients who were in high disease severity (p = 0.0064). Interestingly, the AG genotype (rs3763959) has been associated with a higher presence of bone erosion in RA patients (p = 0.0436). The SNP rs4239242 TT genotype showed a positive association with RA in comparison to the control group. The AG genotype (rs3763959) has been associated with a higher presence of bone erosion in RA patients.